Respostas

A melhor resposta!
2014-08-06T15:08:15-03:00
x- y^{2} =3 ⇒ x= y^{2} +3

\log_2 ( y^{2}+3 )+\log_ \frac{1}{2}  (y+3)=1

\log_2 ( y^{2}+3 )+ \dfrac{\log_ 2  (y+3)}{\log_ 2  \frac{1}{2}} =1

\log_2 ( y^{2}+3 )+ \dfrac{\log_ 2  (y+3)}{\log_ 2   2^{-1} } =1

\log_2 ( y^{2}+3 )+ \dfrac{\log_ 2  (y+3)}{-1.1 } =1

\log_2 ( y^{2}+3 )-\log_ 2  (y+3) =1

\log_2  \frac{y^{2}+3}{y+3} =1

\dfrac{y^{2}+3}{y+3}= 2^{1} =2

y^{2}+3=2y+6

y^{2}-2y-3=0

(y+1).(y-3)=0

y+1=0 ⇒ y=-1 ⇒ x= (-1)^{2} +3=1+3=4
ou
y-3=0 ⇒ y=3 ⇒ x= 3^{2} +3=9+3=12

S = {(x,y) ∈ R | (4, -1), (12, 3)}
1 5 1
Obrigado por marcar como a melhor!